Phase-Sequence of Redroot Pigweed Seed Germination Responses to Ethylene and Other Stimuli - Schonbeck, Mark W. (1981)
Phase-sequence studies showed that light, ethylene, and high temperature each enhanced germination of redroot pigweed (Amaranthus retroflexus L.) seeds when given during the first 24 hours of seed imbibition. Responses were maximal during the first 12 hours. After 48 hours all three stimuli given together caused 75% germination but each alone was ineffective. The main influence of water potential on seed germination occurred at about 24 hours, but the influence of CO(2) extended into the second and third days. Germination was reduced by water stress (−4 bars) or CO(2)-free air, but ethylene reversed the reduction even when administered after several days incubation. This suggested that environmental and hormonal factors affected redroot pigweed seeds at two distinct stages in the sequence of germination events.